(L)-phenylalanine derived Schiff base ligated vanadium(IV) complex as an efficient catalyst for a CO2 fixation reaction. (1st December 2020) - Lahkar, Surabhi; Borah, Rakhimoni; Deori, Naranarayan; Brahma, Sanfaori
Graphical abstract: An efficient CO2 fixation reaction, causing up to 99% conversions of epoxides to cyclic carbonates, is catalyzed by a one pot synthesized oxovanadium(IV) complex consisting of an amino acid derived Schiff base ligand. Highlights: An efficient catalytic reaction of CO 2 with epoxides is reported here. 96-99 % conversions of epoxides to cyclic carbonate products are achieved. Catalytic reactions are done under relatively mild conditions. Catalyst is an ( L )-phenylalanine derived Schiff base ligated oxovanadium(IV) complex. The large amount of catalyst can be synthesized in one pot in a very facile way. The prepared catalyst has been characterised by UV Vis, IR and ESI mass techniques. Catalyst itself has not been crystallographically characterised. However, the X-ray structure of a complex derived from the catalyst is determined. X-ray structure provides indirect evidence for the structure of the catalyst used. Abstract: One oxovanadium(IV) complex containing an ( L )-phenylalanine derived Schiff base ligand has been synthesized and characterized by UV Vis, IR and ESI mass spectrometry. When this complex was kept in methanol for crystallization, brown crystals were obtained. Crystal structure analysis revealed that the original complex crystallized into a new complex. The vanadium(IV) center in the original complex was oxidized to a vanadium(V) center in the new complex. The original complex is shown to be an efficient catalyst for the cycloaddition reaction of CO2 with epoxides to form cyclic carbonates, with up to 99% conversion.